Being Black and Being A Woman: Double Oppression Experience in Angie Thomas’s “On The Come Up” (2019) - Jodi Alfando; Delvi Wahyuni (Universitas Negeri Padang, 2022)
Being black and being a woman is complicated things, especially when the world has dominated by patriarchal ideology and act of racism has been known worldwide in all over the world. Black women are on the verge of getting oppression based on their gender and their ethnicity, it is called double oppression. This research objective is to examine the double oppression that happened to black women in the novel On the Come Up (2019) by Angie Thomas. Black women on the novel have particular signs of double oppression which happened on their daily basis. This research used the Intersectionality Theory proposed by Kimberlè Crenshaw (1989). The use of this theory to determine the double oppression that experienced by black women. This research also applies the five faces of oppression by Iris Marion Young (1990) which are marginalization, exploitation, powerlessness, cultural imperialism, and violence. The data collection was in the form of narrations and dialogues. The findings of this research is the black women in the novel are indeed got oppressed based on their gender and their ethnicity based on the forms of oppression even when they live in the black society. In conclusion, the black women in American society have tendency to be oppressed twice, black women still have a war against oppression even in this modern day when everyone should be treated equally.